Custom in the Function of Protection of Intellectual Property Rights - Festić, Amra (Kriminalističke teme, 2002)
Intellectual property is right to goods and information whose economic value is based on creativity and intellectual work that preceded materialization. From the above we can deduct two main characteristics of intellectual property: non/material (intellectual work) and economic function (market confirmed value). Rights of intellectual property consider rights of the idea owner, patents and other means of creative research. Those who have these rights have the same status as owners of material resources.